Analisis Pengaruh Blackhole Attack Terhadap Kinerja Protokol Routing BATMAN (Better Approach To Mobile Ad Hoc Network) Pada Mobile Ad Hoc Network - Imam Nurhidayat; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mobile Ad-hoc Network (MANET) is a network architecture consisting of several nodes that move freely and communicate with each other. Each node can function as a router or client for other nodes. MANET has 3 types of routing protocols, namely proactive, reactive and hybrid routing protocols. BATMAN (Better Approach to Mobile Adhoc Network) is one of the routing protocols on MANET. In terms of security, MANET is still vulnerable to various forms of attacks, especially against active attacks that can destroy, modify, and delete data and information. One type of active attack that can occurs in MANET is blackhole attack. Blackhole Attack is an attack that can cause loss of data packets. Based on the above problems, the authors made a study entitled Analysis the Effect of Blackhole Attack on the Performance of the BATMAN (Better Approach To Mobile Adhoc Network) Routing Protocol on Mobile Adhoc Network. The results obtained in this study are blackhole attacks affect the performance of the BATMAN routing protocol. Testing is done using OMNET ++ with a test scenario in the form of variations in number of nodes, number of attacking nodes, and area of ​​the simulation. Test parameters used are packet delivery ratio (PDR) and packet loss. The packet loss calculation is only done on packets dropped by the attacker node. The test results show that the lowest packet delivery ratio is 14,24% in the 30 node scenario with an area of ​​1200x1200 m2. While the highest average packet loss is 56.62% in the 30 node scenario with an area of ​​1000x1000 m2.